2015
DOI: 10.1093/brain/awu389
|View full text |Cite
|
Sign up to set email alerts
|

White matter lesional predictors of chronic visual neglect: a longitudinal study

Abstract: Chronic visual neglect prevents brain-damaged patients from returning to an independent and active life. Detecting predictors of persistent neglect as early as possible after the stroke is therefore crucial to plan the relevant interventions. Neglect signs do not only depend on focal brain lesions, but also on dysfunction of large-scale brain networks connected by white matter bundles. We explored the relationship between markers of axonal degeneration occurring after the stroke and visual neglect chronicity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
149
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(170 citation statements)
references
References 113 publications
21
149
0
Order By: Relevance
“…These results confirm models according to which disrupted integrity of right-hemisphere frontoparietal networks is a core pathophysiological mechanism in neglect syndrome (Corbetta and Shulman, 2011;Bartolomeo et al, 2012). So far, a disconnection of right fronto-parietal networks in neglect has been demonstrated at the neuroanatomical and neurofunctional level using in-vivo tractography (Thiebaut de Schotten et al, 2005, 2011, lesion mapping (Ptak and Schnider, 2010;Lunven et al, 2015), fMRI (He et al, 2007;Bartolomeo et al, 2012) and resting state networks analysis of MRI and EEG (Baldassarre et al, 2014;Fellrath et al, 2016). However, the role of transient functional synchronization as a network-based mechanism underlying perceptual deficits in neglect has not been identified.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These results confirm models according to which disrupted integrity of right-hemisphere frontoparietal networks is a core pathophysiological mechanism in neglect syndrome (Corbetta and Shulman, 2011;Bartolomeo et al, 2012). So far, a disconnection of right fronto-parietal networks in neglect has been demonstrated at the neuroanatomical and neurofunctional level using in-vivo tractography (Thiebaut de Schotten et al, 2005, 2011, lesion mapping (Ptak and Schnider, 2010;Lunven et al, 2015), fMRI (He et al, 2007;Bartolomeo et al, 2012) and resting state networks analysis of MRI and EEG (Baldassarre et al, 2014;Fellrath et al, 2016). However, the role of transient functional synchronization as a network-based mechanism underlying perceptual deficits in neglect has not been identified.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, consistent with He et al (2007), in acute and subchronic patients studied here, synchronizations of both dorsal and ventral networks were impaired. Critically, as supported by recent neuroanatomical findings (Lunven et al, 2015), the dysfunction of the right dorsal fronto-parietal pair was specific for neglect and predicted independently symptoms of hemi-neglect.…”
Section: Fronto-parietal Theta Synchronization During Visual Processingsupporting
confidence: 59%
See 1 more Smart Citation
“…With recent advances in diffusion tensor imaging methods, such as the combination of spherical deconvolution (Dell'Acqua et al, 2007) with adaptive regularization to reject spurious non-physiologic fiber orientations it is possible to tease apart the three components of the SLF (Dell'Acqua & Catani, 2012). It has now been reported that SLF II lateralization is correlated with line bisection bias (Thiebaut de Schotten et al, 2011) and that SLFII damage in particular is associated with spatial neglect (Lunven et al, 2015; Thiebaut de Schotten et al, 2014) refining prior results implicating the SLF (Doricchi & Tomaiuolo, 2003; Leibovitch et al, 1998; Urbanski et al, 2008; Urbanski et al, 2011). …”
Section: Introductionmentioning
confidence: 63%
“…Other tracts whose damage has been associated with neglect include more ventral pathways that could be considered part of the VAN (Umarova et al, 2010), These include the Inferior Longitudinal Fasciculus (ILF) (Bird et al, 2006) connecting occipital and temporal lobes, and the Inferior Fronto-Occipital Fasciculus (IFOF) (Catani & Thiebaut de Schotten, 2008; Urbanski et al, 2008) which connects the lateral orbitofrontal cortex and marginal gyrus with the inferior middle occipital, ligual and inferior occipital gyri (Forkel et al, 2014; Lawes et al, 2008). More recently, damage to the splenium of the corpus callosum has also been shown to be associated with chronic neglect (Lunven et al, 2015). …”
Section: Introductionmentioning
confidence: 99%